Does serum 25-hydroxyvitamin D levels have impacts on sarcopenia in patients with chronic heart failure?. (11th May 2022) - Nagaoka, R; Katano, S; Numazawa, R; Kouzu, H; Ohori, K; Honma, S; Kamoda, T; Sato, K; Nishikawa, R; Owada, W; Nagano, N; Koyama, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Sarcopenia is associated with poor functional status and clinical outcomes in heart failure (HF) patients. Although recent observational studies showed the relationship between lower serum vitamin D levels and the development of poor physical function in community-dwelling older adults, involvement of vitamin D status in the development of sarcopenia in HF patients remain unclear. This study aimed to investigate the impact of serum vitamin D concentrations on sarcopenia in patients with HF. Methods: We retrospectively enrolled 269 consecutive patients [median age of 73 years (interquartile range 63-82 years); 35% female] admitted to our institute for diagnosis and management of HF, and received the dual-energy X-ray absorptiometry (DEXA) method during the period from 1 September 2018 to 30 September 2021. The 25-hydroxyvitamin D [25(OH)D] was detected by a chemiluminescence immunoassay (CLIA) technology. The diagnosis of sarcopenia was made according to the criteria of Asia Working Group for Sarcopenia incorporating reduced skeletal muscle mass (appendicular skeletal muscle index [ASMI], <7.00 kg/m2 in males and <5.40 kg/m2 in females), and lower muscle strength (handgrip strength, <28 kg in males and <18 kg in females) and/or poor physical performance (gait speed, <1.0 m/s; chair stand test time, ≥12 s; short physical performance battery, ≤9 points). Results: Of 269 patients, 116 (43%) patients had sarcopenia. An adjusted logistic regression model with a restricted cubic spline function showed that the odds ratio (OR) for sarcopenia increased as the serum 25(OH)D levels decreased. When the value that corresponded to an upper limit of 95% confidence interval (CI) for an OR of 1.0 was defined as the cut-off value of 25(OH)D levels for predicting sarcopenia, it was 18 ng/mL (Figure 1A). A multivariate logistic regression model was fit to calculate the propensity score (PS) for the 25(OH)D levels being <18 ng/mL based on covariates such as age, sex, and N-terminal pro B-type natriuretic peptide. (C-statistics 0.761). The inverse probability of treatment weighting (IPTW) was computed using PS to minimize differences in potential confounding factors between patients with a low serum 25(OH)D levels (<18 ng/mL) and those with a high serum 25(OH)D levels (≥18 ng/mL, Figure 1B). Results of the multivariate logistic regression analysis in the IPTW-weighted patients showed that a low serum 25(OH)D was independently associated with presence of sarcopenia (adjusted OR 2.03, 95% CI 1.31-3.16, p<0.01). In addition, patients with a low serum 25(OH)D had a significantly lower muscle strength and poor physical performance, but not ASMI, than those with a high serum 25(OH)D (Figure 2). Conclusion: Decreased serum 25(OH)D levels are associated with decline in muscle strength and physical performance in HF patients. Serum 25(OH)D levels of <18 ng/mL may be a novel risk factor of sarcopenia in HF patients.